Lacan: A Zoontology (or How My Dog and I Figure in the Anthropocene) - Dela Cruz, Aaron Philip M (Dúnong: UP Diliman Journal of Student Research; Vol 1 (2021), 2023)
“Dogs are not surrogates for theory; they are not here just to think with. They are here to live with. Partners in the crime of human evolution.” – Donna Haraway